Single-Center Experience With Lutonix Drug-Coated Balloons in Infrapopliteal Arteries. (June 2016) - Steiner, Sabine; Schmidt, Andrej; Bausback, Yvonne; Bräunlich, Sven; Ulrich, Matthias; Banning-Eichenseer, Ursula; Scheinert, Dierk
Purpose: To examine patient outcomes following the use of the Lutonix drug-coated balloon (DCB) in patients undergoing endovascular intervention in below-the-knee (BTK) arteries.Methods: A retrospective chart review identified 248 patients who were treated for symptomatic peripheral artery disease with the Lutonix DCB between May 2013 and October 2014. Forty patients were lost to follow-up, leaving 208 patients (mean age 74.1±9.7 years; 138 men) with evaluable data for outcome analysis. The patient cohort suffered from either severe claudication (38.6%) or critical limb ischemia (CLI; 61.4%) in 220 limbs. Almost two-thirds (140, 63.6%) of the 220 target lesions were total occlusions, and 37 (17.8%) of all patients had occlusion of all 3 BTK vessels before intervention.Results: Over a median 9-month follow-up, target lesion revascularization occurred in 15.9% of patients with an average time to first reintervention of 8 months. In total, 39 amputations were performed in 31 limbs. However, 17 of these amputations were preplanned minor amputations below the ankle; only 9 (4.1%) major amputations occurred corresponding to 6.6% of the CLI cohort. Freedom from the composite of death or major amputation was estimated as 92% and 85% at 6 and 12 months, respectively, by Kaplan-Meier analysis. In the full cohort, improvement of at least 1 Rutherford category was seen in 130 (59.1%) limbs after 1 year or at the last follow-up, with 104 (80.0%) of those limbs showing an improvement of ≥2 categories.Conclusion: From this single-center experience, the Lutonix DCB shows therapeutic promise in a disease state where new treatment options are needed.